An exploratory investigation of psychosocial effects of service dogs on veterans’ families from the perspective of family members - Williamson, Linzi; Rath, Grace; Dell, Colleen (Frontiers in Psychology, 2025)
Research on the psychosocial effects of service dogs (SDogs) on veterans’ family members is relatively limited and often centers veterans’ perspectives rather than those of the family. This exploratory study aimed to examine how Canadian veterans’ family members perceive veterans’ SDog and how they affect different psychosocial outcomes, specifically family quality of life and caregiving. A mixed-methods design utilizing an online questionnaire and follow-up interviews was employed. A non-probability sample of veterans’ family members (i.e., spouses, parents, siblings, friends) were recruited via convenience and snowball sampling methods. Participants (N = 35) completed an online questionnaire containing scales measuring their perceptions of and bond with the SDogs, their experience of caregiving, and overall family quality of life. Interviews with veterans’ spouses (N = 7) expanded on these topics. We analyzed quantitative data with descriptive and inferential statistics and qualitative data with content analysis. Overall, family members had positive perceptions of and felt bonded to the SDogs. Caregiver scores were relatively high suggesting risk of burnout. Interviewed participants reported no change in their caregiving duties, but they worried less about the veterans because of the SDog. Family quality of life scores were relatively high and SDogs were generally well-integrated into the family, but families seemed to need some support concerning their own emotional well-being. Findings from this study highlight some of the psycho-social benefits of SDogs for veterans’ families from their perspectives. Optimizing these benefits may require awareness of and managing drawbacks related to SDogs, acknowledging limits of the SDog role, and that SDogs’ role can overlap with that of family pets.